2021
DOI: 10.1111/anu.13316
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary betaine on cholesterol metabolism and hepatopancreas function in gibel carp ( Carassius gibelio ) fed with a high‐fat diet

Abstract: This research aimed to investigate the role of dietary betaine in high-fat diet in cholesterol metabolism in gibel carp. Fish were randomly allocated to five groups and fed with basic diet, high-fat diet and high-fat diet with 1 g/kg, 4 g/kg and 16 g/kg betaine, respectively. The feeding trial lasted 10 weeks. The results showed that though betaine addition decreased fish final body weight, it alleviated lipid metabolism disorder caused by high-fat diet according to serum TC, TG, LDLC and HDLC levels. More imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 42 publications
3
11
0
Order By: Relevance
“…Diet 2 had much less protein deposition than Diet 1, implying that a reduction in protein intake from the diet would lead to a decrease in protein deposition in carp muscle. In gibel carp (Carassius gibelio), similar results were observed [24] and rice field eel [20].…”
Section: Discussionsupporting
confidence: 69%
“…Diet 2 had much less protein deposition than Diet 1, implying that a reduction in protein intake from the diet would lead to a decrease in protein deposition in carp muscle. In gibel carp (Carassius gibelio), similar results were observed [24] and rice field eel [20].…”
Section: Discussionsupporting
confidence: 69%
“…In addition, betaine can regulate digestive enzymes and result in efficient feed digestion (Lim et al, 2022). Besides, betaine is an attractant agent involved in enhancing the feed intake, which is evident in this study (Adjoumani et al, 2017;Dong et al, 2021). Betaine also acts as a methyl donor, which helps with the protein and energy metabolism in fish's entire body (Virtanen et al, 1989).…”
Section: Discussionmentioning
confidence: 77%
“…Betaine has many metabolic roles, including osmoregulation and methyl donor (Virtanen et al, 1989). Further, betaine has attractant and lipid metabolic roles (Adjoumani et al, 2017;Dong et al, 2021). The inclusion of betaine in aquafeed resulted in high feed intake and growth performance of several aquatic animals (Ghosh et al, 2019;Shi et al, 2021).…”
mentioning
confidence: 99%
“…In addition, free radicals react with cell membrane phospholipids (glycerophospholipid synthesis) to produce lipid peroxides ( 75 ). Studies have demonstrated that the downregulation of these proteins reduces lipid peroxidation activity ( 76 , 77 ). Besides, CYP1A1 and GSTT1 were inversely correlated with the AST and ALT.…”
Section: Discussionmentioning
confidence: 99%